PENGARUH PEMBELAJARAN MATA KULIAH KEWIRAUSAHAAN DAN PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA SEMESTER III DAN V PENDIDIKAN EKONOMI STKIP PGRI BANDARLAMPUNG - Karmila, Jacinta (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
This study aims to determine: (1) The Effect of Learning Entrepreneurship Subjects on Entrepreneurial Interest in Semester III and V Economic Education STKIP PGRI Bandarlampung Academic Year 2019/2020; (2) The Effect of Entrepreneurship Practices on Entrepreneurial Interests of Semester III and V Economic Education of STKIP PGRI Bandarlampung in the 2019/2020 Academic Year; (3) The Effect of Subject Learning and Entrepreneurship Practices together on Entrepreneurial Interest in Semester III and V Economic Education STKIP PGRI Bandarlampung Academic Year 2019/2020. This quantitative study used a sample of semester III and V students with a total sample of 105 respondents. Data collection on entrepreneurship subject learning, entrepreneurial practices and interest in entrepreneurship uses a questionnaire, while the sampling technique uses simple random sampling. Tests carried out include multiple regression tests, t tests, F tests, and the coefficient of determination (R2). Based on the results of the study, it can be concluded that: 1) learning entrepreneurship courses significantly influence student interest in entrepreneurship with a tcount of 2.219> ttable of 1.984 with a significant value of 0.000 <0.05; 2) the practice of entrepreneurship has a significant effect in fostering student entrepreneurial interest with a tcount of 3.343> ttable of 1.984 with a significant value of 0.000 <0.05. Based on the results of the F test, simultaneous learning of entrepreneurship courses and entrepreneurial practice significantly influence students' interest in entrepreneurship. The coefficient of determination is 0.347, which means that the influence of entrepreneurship learning subjects and entrepreneurial practice in fostering entrepreneurial interest in semester III and V STKIP PGRI Bandarlampung Economic Education is 34.7%, while the remaining 65.3% is influenced by variables not examined in this study.